2023
DOI: 10.3390/diagnostics13172814
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Link between Polycystic Ovary Syndrome and Kidney Stones: Finding from the Tehran Lipid and Glucose Study (TLGS)

Marzieh Rostami Dovom,
Maryam Rahmati,
Saber Amanollahi Soudmand
et al.

Abstract: Background: We aimed to investigate the association between kidney stones and polycystic ovarian syndrome (PCOS). Materials and methods: In a cross-sectional study, data from the Tehran Lipid and Glucose Study (TLGS) were used to investigate the risk of kidney stones in women with Polycystic Ovary Syndrome (PCOS). Four distinct phenotypes of PCOS, as defined by the Rotterdam criteria, were examined in a sample of 520 women and compared to a control group of 1638 eumenorrheic non-hirsute healthy women. Univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Huang et al raised that serum TST may be a protective factor in men over 40 years too [42]. However, recent researches have suggested that female patients with PCOS are two to three times more likely to develop kidney stones [20] and that low serum magnesium status in these patients may be associated with higher testosterone levels [47]. It appears that these results are inconsistent with ours, but it is worth note that patients with PCOS, which is characterized by chronic low-level in ammation [48], are prone to suffer from kidney stone formation resulting from immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al raised that serum TST may be a protective factor in men over 40 years too [42]. However, recent researches have suggested that female patients with PCOS are two to three times more likely to develop kidney stones [20] and that low serum magnesium status in these patients may be associated with higher testosterone levels [47]. It appears that these results are inconsistent with ours, but it is worth note that patients with PCOS, which is characterized by chronic low-level in ammation [48], are prone to suffer from kidney stone formation resulting from immune dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Through different mechanisms, a low magnesium state leads to poor urinary magnesium excretion and leads to urinary calcium oxalate supersaturation with an increased likelihood of formation of insoluble complexes [19]. It has recently been reported in the literature that women with polycystic ovary syndrome (PCOS), particularly those who present with irregular menstruation and polycystic ovary morphology (PCOM) on ultrasound, have a higher likelihood of developing kidney stones [20].…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] These conditions have the potential to cause alterations in kidney function, characterised by the presence of protein in the urine and changes in some kidney function parameters. [ 27 ] The changes in serum creatinine, eGFR and/or blood urea nitrogen from peripheral blood can be used to depict the reduction of kidney function. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%